Design and test of 4ZZ-4A2 full-hydraulic self-propelled jujube harvester - Fu, Wei; Zhang, Zhiyuan; Ding, Kai; Cao, Weibin; Kan, Za; Pan, Junbing; Liu, Yudong (International Journal of Agricultural and Biological Engineering, 2018)
The cultivated area of jujube in Xinjiang has increased rapidly in recent years. While the jujube harvest by hand has the shortage of high labor intensity, low efficiency and high labor cost, in addition, the harvesting machinery applying to dwarf and dense planting mode of jujubes is unavailable in Xinjiang. The 4ZZ-4A2 based on the full-hydraulic self-propelled jujube harvester was designed to solve the above problems. The harvester was mainly composed of a frame, a vibrating device, a jujube collecting and conveying device, an air separation device, a steering system, a hydraulic system and a jujube suction device and was capable of completing vibration, collection, conveying, cleaning and sundries removal work of jujubes through one step. The jujubes dropped on the ground were picked up at the same time. The AMESim simulation software was adopted to perform simulation analysis on the overall hydraulic system. The results showed that the speed of the vibrating motor was stable at about 650 r/min (the corresponding vibration frequency is 10.83 Hz) with the torque of 80 N·m, the speed of the conveyor motor was stable at 77 r/min with the torque of 77 N·m; the speed of the fan motor was stable at 54 r/min with the torque of 53.6 N·m; the speed of the walking motor fluctuated around 100 r/min with the torque of about 1000 N·m; the hydraulic steering system responded rapidly and could satisfy the actual working requirements of the jujube harvester. The jujube garden test results showed that the harvester could reach to the optimum harvesting effect when running at the speed of 0.5 m/s. Under such speed, the ground jujube picking rate was 45.1%, the tree jujube harvesting rate was 93.2%, the loss rate was 2.9%, and the damage rate was 0.9%. This study can provide theoretical basis and technical support for the jujube harvester.Keywords: harvester, jujube, hydraulic simulation, dwarf and close planting, designDOI: 10.25165/j.ijabe.20181104.3981Citation: Fu W, Zhang Z Y, Ding K, Cao W B, Kan Z, Pan J B, et al. Design and test of 4ZZ-4A2 full-hydraulic self-propelled jujube harvester. Int J Agric & Biol Eng, 2018; 11(4): 104-110.